I am just wondering the author is doing in this calculation step.(adsbygoogle = window.adsbygoogle || []).push({});

Given ##\displaystyle \rho A \frac {\partial^2 w}{\partial x^2} - \rho I \frac{\partial^4 w}{\partial t^2 \partial x^2} +\frac {\partial^2 }{\partial x^2}EI \frac {\partial^2 w}{\partial x^2}=q(x,t)##

where ##w(x,t)=W(x)e^{-i \omega t}##

##\omega## is the frequency of natural transverse motion and ##W(x)## is the mode shape of the transverse motion.

He substitutes the above into the PDE to get the following

##\displaystyle \frac {d^2 }{d x^2}EI \frac {d^2 W}{d x^2} - \lambda (\rho A W -\rho I \frac {d^2 W }{d x^2} ) =0## where ##\lambda=\omega^2##

However, I calculate the second derivative ##w''(x)=e^{-i\omega t} W''(x)## and ##w''(t)=- \lambda e^{-i\omega t} W(x)##

What is incorrect on my part? Ie, where did the exponentials go?

thanks

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Natural Vibration of Beam - PDE

**Physics Forums | Science Articles, Homework Help, Discussion**